KONSEP DIRI MAHASISWA UNIVERSITAS PASUNDAN DALAM KONTEKS KOMUNIKASI ANTARBUDAYA - Rahmi Aini; Teuku Yuliansyah; Aura Angelisa; Feni Oktami Putri (Linimasa : Jurnal Ilmu Komunikasi, 2023)
University development and competition, both public and private, to be the best is now required. Each of these institutions, whether a university, institute, or high school, is required to be able to win interest and trust from the public, so it must pay attention and maintain good quality for its users. Organizational culture has an important role in an organization. Pasundan University implements three pillars in its organizational culture, namely "Nyunda, Nyantri, and Nyakola." Pasundan University, especially in the Communication Science Study Program, has various kinds of students from various regions who have their own cultures and habits. Cultural diversity is both a potential and a puzzle that always necessitates problem solving. Any uniqueness or something that implies the peculiarity of an area is basically wealth. The conception of a multicultural Indonesia is not only at the physical level but also at the level of consciousness. Indonesia, as an archipelagic country that has various cultures and customs, has as its motto "Bhineka Tunggal Ika," which means different but still one.